Implementation of a multimodal home-based rehabilitation intervention after discharge from inpatient geriatric rehabilitation (GeRas): an early qualitative process evaluation - Roth, Catharina; Maier, Leonie; Abel, Bastian; Roigk, Patrick; Rapp, Kilian; Schmidberger, Oliver; Bongartz, Martin; Maier, Simone; Wirth, Isabel; Metz, Brigitte; Immel, Désirée; Finger, Benjamin; et al. (BMC geriatrics, 2024)
Geriatric rehabilitation aims at increasing physical and social activity and maintaining the functional reserve of older people. However, the continuity of geriatric rehabilitation in the outpatient setting is limited due to a lack of structured aftercare programs. In order to overcome this, a three-month multimodal home-based intervention program (GeRas) was implemented. The aim of this early qualitative process evaluation was to assess GeRas in terms of perceived reach, effectiveness/efficacy, adoption/uptake, implementation, and maintenance/sustainability (Domains within the RE-AIM Framework) from the perspective of patients who received the intervention and healthcare providers who were involved in the delivery of the intervention.
Gesehen am 03.03.2025